Sulfur metabolism, organic acid accumulation and phytohormone regulation are crucial physiological processes modulating the different tolerance to Pb stress of two contrasting poplars. (21st March 2022) - Shi, Wenguang; Li, Jing; Kan, Donxu; Yu, Wenjian; Chen, Xin; Zhang, Yuhong; Ma, Chaofeng; Deng, Shurong; Zhou, Jing; Fayyaz, Payam; Luo, Zhi-Bin
Abstract: To investigate the pivotal physiological processes modulating lead (Pb) tolerance capacities of poplars, the saplings of two contrasting poplar species, Populus × canescens with high Pb sensitivity and Populus nigra with relatively low Pb sensitivity, were treated with either 0 or 8 mM Pb for 6 weeks. Lead was absorbed by the roots and accumulated massively in the roots and leaves, leading to overproduction of reactive oxygen species, reduced photosynthesis and biomass in both poplar species. Particularly, the tolerance index of P. × canescens was significantly lower than that of P. nigra . Moreover, the physiological responses including the concentrations of nutrient elements, thiols, organic acids, phytohormones and nonenzymatic antioxidants, and the activities of antioxidative enzymes in the roots and leaves were different between the two poplar species. Notably, the differences in concentrations of nutrient elements, organic acids and phytohormones were remarkable between the two poplar species. A further evaluation of the Pb tolerance-related physiological processes showed that the change of 'sulfur (S) metabolism' in the roots was greater, and that of 'organic acid accumulation' in the roots and 'phytohormone regulation' in the leaves were markedly smaller in P. × canescens than those in P. nigra . These results suggest that there are differences in Pb tolerance capacities between P. × canescens and P. nigra, which is probably associated with their contrasting physiological responses to Pb stress, and that S metabolism, organic acid accumulation and phytohormone regulation are probably the key physiological processes modulating the different Pb tolerance capacities between the two poplar species.